2016
DOI: 10.1589/jpts.28.2772
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise types for rotator cuff repair patients on activities of shoulder muscles and upper limb disability

Abstract: [Purpose] This study investigated the effect on activities, shoulder muscle fatigue, upper limb disability of two exercise types performed by patients in the post- immobilization period of rotator cuff repair. [Subjects and Methods] The intervention program was performed by 20 patients from 6 weeks after rotator cuff repair. Ten subjects each were randomly allocated to a group performing open kinetic chain exercise and a group preforming closed kinetic chain exercise. Muscle activity and median frequency were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The difference in muscle strength between a healthy shoulder and an injured shoulder in patients with rotator cuff tendinopathy probably results in a difficulty to apply the correct technique during moderate-high intensity resistance exercises that requires flexion and extension of the shoulder [30]. In turn, rotator cuff rupture produces changes in kinematic function, accompanied by shoulder pain and atrophy of the surrounding musculature [31]. Initial treatment may not always be surgical, depending on the activity level and tear size [32].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in muscle strength between a healthy shoulder and an injured shoulder in patients with rotator cuff tendinopathy probably results in a difficulty to apply the correct technique during moderate-high intensity resistance exercises that requires flexion and extension of the shoulder [30]. In turn, rotator cuff rupture produces changes in kinematic function, accompanied by shoulder pain and atrophy of the surrounding musculature [31]. Initial treatment may not always be surgical, depending on the activity level and tear size [32].…”
Section: Discussionmentioning
confidence: 99%
“…Ha et al 1 ) previously reported positive effects of the SWE in a selective strengthening exercise program for the infraspinatus muscle. Kang et al 2 ) reported that the infraspinatus muscle activity increased significantly but that posterior deltoid muscle activity did not after subjects performed an intervention involving shoulder external rotation in a standing position with the shoulder at 90° flexion. Lim et al 10 ) investigated the activities of two muscles with and without visual feedback using EMG signal input to the computer monitor, and reported that the ratio of the infraspinatus to posterior deltoid activity was greater with visual feedback than without it.…”
Section: Discussionmentioning
confidence: 99%
“…During shoulder movements, the rotator cuff (RC) provides stability for glenohumeral joint and functions as an approximation force to resist dislocation or subluxation of humerus 1 , 2 ) . When the RC is injured, the range of shoulder motion is limited and prone to instabilty during movements.…”
Section: Introductionmentioning
confidence: 99%
“…Post-training muscle damage is thought to be associated with decreased performance and an increased risk of injury, and effective management of this condition is essential for rehabilitation, health promotion, and improved performance in athletic competition. In particular, for the upper extremities, muscle fatigue affects the ability to perform movements, suggesting the need for recovery from muscle fatigue in performing upper extremity tasks in patients with rotator cuff injury 2 ) . Therefore, it is important to provide appropriate post-training muscle recovery and strengthening to the upper extremities.…”
Section: Introductionmentioning
confidence: 99%